Кома: [повести] / Андрей Кивинов - Кивинов Андрей Владимирович (Уголовное дело, 2002)
Экземпляры: Ф28 (20191203) / Инвентарный номер: 58685 / Цена: 25.00 / Сис.шифр: Р2 / Авт.знак: К 38 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6